Bullous Scabies in an Immunocompromised Host - James R. Wester; Lesley E Jackson; Kathryn Mokgosi; Tomer Barak; Mahmoud Abu Hazeem (Case Reports in Infectious Diseases)
A 40-year-old woman with a history of poorly controlled HIV presented to a district referral hospital in rural Botswana for a generalized skin rash of several months duration. The highly pruritic rash predominantly involved her hands and feet and was associated with bullae that were present for days at a time before rupturing without drainage or discharge. The patient endorsed night sweats, periodic fevers, occasional cough productive of blood-tinged sputum, fatigue, and weight loss. On admission, CD4 count was 46 cells/mm3 and viral load was >750000 copies/mL. Pulmonary tuberculosis testing via sputum was negative twice. A blood count demonstrated eosinophilia. Oral acyclovir was started empirically for disseminated herpes virus infection, with topical beclomethasone and intravenous antibiotics for possible superinfected bullous dermatosis. With inadequate response to treatment, a skin biopsy was obtained and microscopic examination demonstrated scabies mites. The absence of skin burrows, the presence of bullae, and working in a low-resource setting without direct access to microscopic examination delayed diagnosis. The patient was initiated on topical permethrin. Oral ivermectin was not available in country and was obtained from overseas shipment, delaying treatment initiation. Drastic improvement was seen after the patient initiated ivermectin. A local nurse in the patient’s village visited her community and found multiple individuals with active scabies infection. The patient’s discharge was delayed until these community members were treated successfully with topical permethrin. This case describes an atypical presentation of scabies in an under-resourced setting, demonstrating unique diagnostic, therapeutic, and public health challenges.